FACTORS AFFECTING THE COMPLIANCE AND UTILISATION OF ANTENATAL CARE (ANC) IN BOTH HIGH INCOME COUNTRIES AND LOW-MIDDLE INCOME COUNTRIES: A SYSTEMATIC REVIEW - Petra Ade Paramita Lestari; Adang Bachtiar (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Every pregnancy has its own risk related to unwanted complication. ANC or antenatal care is a program to help the improvement of both pregnancy experience and ensure the health of a baby. ANC itself has been practiced since 100 years ago, a heritage process from the European community, which facilitates pregnant women during the pregnancy to have 12 visitations to nearby health facility. However, reasoning behind such intervention was unknown. As time goes by, many researches, evaluation, and review have been done regarding the content of visitations, amount of attendance each pregnant women need to do during pregnancy period, and further outcome of ANC program. This review is done to clarify ANC program throughout countries with high, middle and low income in the world and gather knowledge from such experience. Methods: Review was done by using databases such as PubMed, Springerlink, and proquest with keyword factors related to utilization of ANC as intervention and mother's compliance, years of publication and PRISMA method. Results: Out of all 33 articles obtained, 12 articles were chosen as other article did not comply to the selection criteria such as year of publication and the content. Variations among different countries in such studies occurred in factors such as the program itself, subject compliance towards the study, and the number of attendees. Furthermore, technologies such as instant messages and internet was also utilized in some programs. Among many factors related to the utilized and compliance of pregnant mother, each country policies, lifestyle, education level, and family incomes played a major role in such differentiation. Furthermore, perception of mother towards the program will also affect her motivation. Conclusion: Although the implementation of ANC in many countries still varies, there were many positive evidences to support the utilization of ANC. Surrounding communities could implement the program if it is suitable to the individuals. Monitoring and evaluation of such program also need to be done.